(untitled) (Eurasian Research Bulletin, 2022)
Today, one of the areas of modernization of school education is the introduction of computer technology and multimedia. This allows you to activate the analytical activity of students, reveal the creative possibilities of students, stimulate the development of mental processes, thinking, perception, memory of students. The article discusses identifying the effectiveness of the use of ICT in the English lesson and their impact on increasing the cognitive activity of students.